How automation and digital disruption are shaping the workforce of the future. Issue 6 (11th November 2019) - Card, Debora; Nelson, Craig
Abstract : Purpose: With the US unemployment rate at 50-year lows and the increased use of automation expected to force organizations to replace or retrain over 25 per cent of their workforce, enterprises need new ways to re-skill employees to prepare for future needs. Design/methodology/approach: The authors spoke with HR leaders of different enterprises to see how they will adapt to the future of work with the combination of automation in the workplace. After gaining insights from multiple sources, they were able to come to some conclusions on how the future of work is shaping up to be. Findings: After gaining insights, they were able to find that companies that seek to combine the best of human ingenuity, empathy and change resilience with the prudent use of automation and re-skilling will be leading the workforce of the future. Originality/value: This paper from ISG was created to give insights into Strategic HR Review from real customers and research conducted. This paper gives valuable insights on how enterprises are actually re-skilling employees to adapt to the rise of automation and IT skills gap.